OUTCOME-BASED EDUCATION (OBE) MOBILE APPLICATION - FINA SYAZARINA, LET (Universiti Malaysia Sarawak (UNIMAS), 2018)
This final year project presents outcome-based education (OBE) learning system especially in Faculty of Engineering, University of Malaysia Sarawak. Research area regarding this project has been identified before start writing and doing simulation for the final year project. All information from previous research related to OBE learning system is gathered directly from supervisor. Mobile application interface is designed and developed by using Android Studio software. The mobile application is developed in order to assist students and staffs in Faculty of Engineering, University of Malaysia Sarawak to obtain information regarding OBE easily. The mobile application has been successfully developed by using Android Studio software.